2021
DOI: 10.1128/msystems.00394-21
|View full text |Cite
|
Sign up to set email alerts
|

A Scale-Free, Fully Connected Global Transition Network Underlies Known Microbiome Diversity

Abstract: Microbiomes are inherently linked by their structural similarity, yet the global features of such similarity are not clear. Here, we propose as a solution a search-based microbiome transition network.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Co-occurrence network analysis revealed that different topological characteristics between UN and HC groups might be linked to different inter-species interactions or system efficiency [ 38 ]. Although the gut microbiota networks in both groups had scale-free properties, the hub nodes, which play a critical role in preserving the overall functionality of the network, were different [ 39 41 ]. Notably, the gut microbiota network of undernourished children exhibited higher clustering coefficient and modularity, along with lower graph density, lower average degree, and longer average path length.…”
Section: Discussionmentioning
confidence: 99%
“…Co-occurrence network analysis revealed that different topological characteristics between UN and HC groups might be linked to different inter-species interactions or system efficiency [ 38 ]. Although the gut microbiota networks in both groups had scale-free properties, the hub nodes, which play a critical role in preserving the overall functionality of the network, were different [ 39 41 ]. Notably, the gut microbiota network of undernourished children exhibited higher clustering coefficient and modularity, along with lower graph density, lower average degree, and longer average path length.…”
Section: Discussionmentioning
confidence: 99%
“…Massive data sets suggested that microbiome structures are intensively distinct across habitat types ( 9 , 18 ). Different microbes have their preference for the 16S rRNA gene variable region in amplification sensitivity and nucleotide sequence recognizability.…”
Section: Resultsmentioning
confidence: 99%
“…Massive data sets suggested that microbiome structures are intensively distinct across habitat types ( 18 ), causing microbes that are unevenly distributed ( 9 ). For instance, Firmicutes and Bacteroidetes dominate the human gut microbiota, while Proteobacteria and Cyanobacteria are prevalent in natural environments ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate the performance of the proposed community detection algorithm MCCD-WN, we used the LFR benchmark (Lancichinetti et al, 2008 ; Lancichinetti and Fortunato, 2009 ), which is a generalization of Girvan-Newman benchmark (Girvan and Newman, 2002 ) and assumes a power-law degree distribution of the nodes, similar to biological networks (Jing et al, 2021 ). The LFR benchmark uses a parameter called mixing parameter (μ w ) which is delineated as the ratio of the external degree of a node to the total degree of the node.…”
Section: Methodsmentioning
confidence: 99%